ANALISIS KESESUAIAN FUNGSI KAWASAN HUTAN DI DESA MANDALLE KECAMATAN MANDALLE KABUPATEN PANGKAJENE DAN KEPULAUAN - Sitti Fatimah; Naufal Naufal; Andi Azis Abdullah; Hasanuddin Molo; Sultan Sultan (Jurnal Belantara, 2023)
The determination of forest areas in 1982, which is the basis for the function of forest areas, is currently considered to be less relevant, this is due to the large number of activities that are not in accordance with their designation and the presence of a new policy of the Ministry of Agriculture in 2021 where forest areas need to be reviewed using predetermined criteria. This study aims to determine the suitability of function of forest areas in Mandalle Village, which is currently based on the Decree of the Minister of Environment and Forestry number SK.362/MENLHK/SETJEN/PLA.0/5/2019 is a Protected Forest Area(Hutan Lindung). This research method uses the method of scoring forest areas with 3 (three) parameters, namely marbles, soil type and rainfall. From the results of this analysis, it is known that the steep slope class (25-40%) covers an area of 90.64 hectares with a percentage of 35.29% and the smallest the Flat slope class (0-8%) covers an area of 3.69 hectares with a percentage of 1.44%. The average rainfall at the study site was 14.78 mm / day (low) and the soil type of the study site was Podzolic which was categorized as sensitive soil.The results showed that the Protected Forest Area in Mandalle Village Mandalle Subdistrict Pangkajene and Islands Regency an area of ± 70,66 hectares (27,52%) suitable as Protected Forest, an area of ± 157,44 hectares (61,31%) directed as a Fixed Production Forest and an area of ± 28,69 hectares (11,17%) is directed as a Convertible Production Forest.